2023
DOI: 10.1097/rlu.0000000000004910
|View full text |Cite
|
Sign up to set email alerts
|

68Ga-DOTA-FAPI-04 PET/CT in the Detection of Thoracic SMARCA4-Deficient Undifferentiated Tumor

Xiuling Shen,
Zhi Yang,
Nan Li

Abstract: Thoracic SMARCA4-deficient undifferentiated tumor (SMARCA4-UT) is a rare malignant disease. We present the case of a 56-year-old woman with thoracic SMARCA4-UT presenting as a mediastinal mass who underwent 68Ga-DOTA-FAPI-04 PET/CT imaging. Intense 68Ga-DOTA-FAPI-04 uptake was observed in the primary tumor and lymph node metastases. After 7 cycles of immune checkpoint inhibitor plus chemotherapy, the patient underwent mediastinal mass resection, and postoperative pathology confirmed a complete pathologic respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Previous studies have shown the usefulness of 18 F-FDG PET/CT in the evaluation of SMARCA4-dUT 5,6 . Recent studies have reported that 68 Ga-FAPI PET/CT may be useful for the diagnosis of SMARCA4-dUT and may even be more advantageous over 18 F-FDG for detecting metastatic lesions 7,8 . In this case, 68 Ga-FAPI-46 PET/CT detected the occult SMARCA4-dUT located in the left pulmonary hilum, which was not visualized by 18 F-FDG PET/CT.…”
mentioning
confidence: 68%
“…Previous studies have shown the usefulness of 18 F-FDG PET/CT in the evaluation of SMARCA4-dUT 5,6 . Recent studies have reported that 68 Ga-FAPI PET/CT may be useful for the diagnosis of SMARCA4-dUT and may even be more advantageous over 18 F-FDG for detecting metastatic lesions 7,8 . In this case, 68 Ga-FAPI-46 PET/CT detected the occult SMARCA4-dUT located in the left pulmonary hilum, which was not visualized by 18 F-FDG PET/CT.…”
mentioning
confidence: 68%
“…Typically, SMARCA4-UT has a strong FDG affinity, making PET a useful tool for clinical staging in addition to CT scans [ 3 ] ( Table 1 ). Recently, Shen et al described a case of SMARCA4-UT that presented as a mediastinal mass and lymph node metastases with intense 68 Ga-DOTA-FAPI-04 uptake, providing new insights into the diagnosis and monitoring of this tumor [ 56 ]. Furthermore, if uptake of 68 Ga-DOTA-FAPI-04 can be demonstrated in other SMARCA4-UT patients, new therapeutic approaches might be used for them.…”
Section: Clinical Pathological Featuresmentioning
confidence: 99%